A comparative study on the insecticidal property of Bambusa vulgaris and Bambusa malingensis shoot and leaf extract against green leafhopper (Nephotettix virescens) - Romel Leo B. Alojado; Glennise Faye C. Mejica; Rj Junsay; Francis Ann Siosan; Nolan C. Tolosa (Maejo International Journal of Energy and Environmental Communication, 2021)
Rice is considered one of the staple foods in Southeast Asian countries, most especially in the Philippines. There are many factors needed to be considered in growing rice crops: the soil nutrient, the climate, the water supply, and the fertilizer used as a supplement to crop growth. But one important thing that farmers should consider is the infestation of pests, specifically the green leafhoppers, which is the primary carrier of tungro virus. This virus affects the growth and development of rice crops. This study aims to investigate the insecticidal effect of Bambusa vulgaris and Bambusa malingensis shoot and leaves extract against green leafhoppers (Nephotettix virescens). The extract was obtained by the decoction method. Phytochemical analysis of the two bamboo species has been carried out, as it was found out that both of them contains alkaloids, flavonoids, and glycosides. The results showed that both the shoot and leaves extract of Bambusa vulgaris and the shoot extract of Bambusa malingensis have potential insecticidal activity against Nephotettix virescens. Further research is needed to identify other factors that could strengthen the effectiveness of applying the extract to the insect specimen.